Evaluation of Factors Influencing Switching Behaviour by Ghana Commercial Bank Customers - Kofi Nyarko, Israel (British Journal of Marketing Studies, 2015)
This study seeks to determine the factors which influence the switching behaviour of customers of Ghana Commercial Bank, Limited in Ho. A descriptive, cross-sectional survey was conducted among 350 purposively selected individual customers. Logistic regression analysis was used to identify the predictors of switching intentions among customers. Results show that four factors; X1 (High transaction fee), X4 (Attractiveness of alternatives), X7 (Inconvenience of bank location) and X9 (Inability to respond to system failure quickly) were statistically significant in the prediction of customer switching with a predicted switching rate of 82.29%. It is suggested there is a need for banks to review their bank charges or transaction fees in the banking sector since high transaction fees have an impact on customer switching behaviour. Also, management should establish more branches in the same township since customers switch in the inception of convenience in the services and location of the banks. Finally, banks should regularly update their system and also employed welled trained staff who will respond to system failure quickly. In addition, they should strive to provide the greatest possible customer satisfaction and convenience them that they have greater customer satisfaction than competitive banks.